Does a coxib-associated thrombotic risk limit the clinical use of the compounds as analgesic anti-inflammatory drugs? - Mukherjee, Debabrata (Thrombosis and Haemostasis, 2006)
Non-steroidal anti-inflammatory agents (NSAIDs) and selective cyclooxygenase (COX-2) inhibitors (coxibs) are commonly used as analgesic and anti-inflammatory agents.Selective COX-2 inhibitors or coxibs were primarily developed asa response to the gastrointestinal toxicity of conventional NSAIDs but may have other side effects. Currently available data suggests definite prothrombotic risk with the coxibs, and the magnitude of risk may vary with individual agents. Based on available data, coxibs should be restricted to use as 2nd-line, possibly as 3rd-line, agents for carefully chosen patients and randomized trials versus placebo or an accepted comparator must be performed to define the overall safety profile in diverse patient populations.The recently announced Prospective Randomized Evaluation of Celecoxib Integrated Safety vs. Ibuprofen or Naproxen (PRECISION) trial will assess the relative cardiovascular safety of three of the most commonly used pain relievers in the treatment of arthritis patients,ibuprofen,naproxen and celecoxib.The study will enroll patients with osteoarthritis, the most common form of arthritis, who have known coronary heart disease or who have multiple risk factors for heart disease and also some patients with rheumatoid arthritis. Patients will be followed for an average of two years to track the occurrence of serious cardiovascular events, including death, heart attack and stroke. This study should provide some definitive evidence of the relative cardiovascular safety of the available anti-inflammatory agents but would be even more useful if it included an arm where patients were treated with analgesics such as acetaminophen and/or moderate strength narcotics.
Keywords: Acute myocardial infarction; coxib; atherothrombosis; cyclooxygenase-2; prothrombotic